2014
DOI: 10.1177/0002716214521993
|View full text |Cite
|
Sign up to set email alerts
|

Conflict and Agency among Sex Workers and Pimps

Abstract: The dominant understanding in the United States of the relationship between pimps and minors involved in commercial sex is that it is one of “child sex trafficking,” in which pimps lure girls into prostitution, then control, exploit, and brutalize them. Such narratives of oppression typically depend on postarrest testimonials by former prostitutes and pimps in punishment and rescue institutions. In contrast, this article presents data collected from active pimps, underage prostitutes, and young adult sex worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(32 citation statements)
references
References 21 publications
0
29
0
3
Order By: Relevance
“…The role of traffickers or pimps seems to be more complicated in DMST than in international sex trafficking. Individuals responsible for trafficking these youth have been found to be family members, acquaintances, and peers who utilize their relationship to facilitate the exploitation (Cole and Sprang 2015;Reid et al 2015), some youth operate without an identified third party, and some evidence suggests that in some cases the role of the third party trafficker/pimp may be less prominent than commonly assumed (Marcus et al 2014).…”
Section: Structural Inequities and Domestic Minor Sex Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of traffickers or pimps seems to be more complicated in DMST than in international sex trafficking. Individuals responsible for trafficking these youth have been found to be family members, acquaintances, and peers who utilize their relationship to facilitate the exploitation (Cole and Sprang 2015;Reid et al 2015), some youth operate without an identified third party, and some evidence suggests that in some cases the role of the third party trafficker/pimp may be less prominent than commonly assumed (Marcus et al 2014).…”
Section: Structural Inequities and Domestic Minor Sex Traffickingmentioning
confidence: 99%
“…The sexual acts that youth are coerced to perform in both of these situations may be similar, however, the extent of the abuse and its context can draw attention to some critical differences. The perpetrator's relationship to the youth is usually distinctive, the number of different partners/perpetrators is usually higher with DMST, the trauma may be more extreme, and, confusingly, in DMST the victim may not perceive him/herself as a victim but as a willing participant who has chosen to engage in these acts (Hartinger-Saunders et al 2017;Marcus et al 2014;National Human Trafficking Resource Center 2017). In child sexual abuse cases to which a child protective service agency generally responds, the perpetrator usually has to be someone who is responsible for the care or supervision of the child or youth (Hartinger-Saunders et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…En el medio académico el comercio sexual de menores ha sido examinado a través de un paradigma dominante sustentado en la categoría "explotación sexual comercial infantil" (Estes et al 2008;Casillas 2008;Reid 2011;Grace et al 2012) y en la categoría "trabajo sexual juvenil" sostenida por un número muy reducido de académicos (Katsulis 2010;Marcus et al 2014). La primera no encuentra diferencias entre modos forzados y no forzados, mientras que la última subraya la especificidad de los modos no forzados.…”
Section: Conceptualización De La Prostitución De Menoresunclassified
“…La categoría "trabajo sexual juvenil" subraya un escenario más complejo que comporta los siguientes elementos: 1/ el menor es víctima de sus propias circunstancias; ii./ los menores en la industria de la prostitución no constituyen una categoría homogénea; iii./ la prostitución juvenil no constituye siempre trata de personas; iv./ el menor es víctima y agente autónomo, y v./ no solo el menor es víctima del cliente; sino que también el cliente puede ser víctima del menor (Katsulis 2010;Marcus et al 2014). …”
Section: Conceptualización De La Prostitución De Menoresunclassified
See 1 more Smart Citation